Clinical and biochemical profile of wasp sting patients in a tertiary care hospital - Parash Ullah; Habiba Kabir; M. M. Jahangir Alam; Md. Shafiqul Bari; Fazle Rabbi Chowdhury (Bangabandhu Sheikh Mujib Medical University Journal)
Background: Wasp stings and the resulting allergic reactions are common reasons for visiting the emergency department. Stings can be fatal due to multi-system involvement. In our country, the impact of massive wasp stings has been significantly underestimated and has not been systematically investigated. This study aimed to identify the clinical presentations and biochemical profiles of patients experiencing wasp stings in our context.